2015
DOI: 10.1007/s11101-015-9411-7
|View full text |Cite
|
Sign up to set email alerts
|

The Brazilian Amaryllidaceae as a source of acetylcholinesterase inhibitory alkaloids

Abstract: Nine Brazilian Amaryllidaceae species were studied for their alkaloid composition and acetylcholinesterase (AChE) inhibitory activity via GC-MS and a modified Ellman assay, respectively. A total of thirty-six alkaloids were identified in these plants, of which Hippeastrum papilio and H. glaucescens exhibited the highest galanthamine content and the best IC 50 values against AChE. Furthermore, Hippeastrum vittatum and Rhodophiala bifida also showed notable AChE inhibitory effects. X-ray crystallographic data fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…The purity of the alkaloid was checked by means of chromatographic (TLC, HPLC), and spectroscopic methods ( 1 H NMR). It was possible to confirm the identity of the product by comparison with galantamine data obtained in the literature (de Andrade et al, 2015).…”
Section: Methodsmentioning
confidence: 83%
“…The purity of the alkaloid was checked by means of chromatographic (TLC, HPLC), and spectroscopic methods ( 1 H NMR). It was possible to confirm the identity of the product by comparison with galantamine data obtained in the literature (de Andrade et al, 2015).…”
Section: Methodsmentioning
confidence: 83%
“…Studies have suggested that there is an important role of GABAergic neurotransmission in stress, anxiety, and epilepsy. GABAergic neurotransmission dysfunction has been reported in the patients of anxiety which is associated with epilepsy 88 . It has been reported through experimental investigation that montanine protected against convulsions by modulating the neurotransmitter systems including GABA A receptors 44 .…”
Section: Montaninementioning
confidence: 99%
“…vulgaris Bernh. 19 A broad spectrum of physiological and medicinal properties were attributed to the species of this family including the following: anti-inflammatory (Liu et al, 2015), acetylcholinesterase inhibitory, 20 immunostimulatory, and DNAbinding activities. Phytochemical analysis showed that the major components of F. vulgarisʼs volatile oil belong to sesqui-and mono-terpene groups of chemicals.…”
Section: Introductionmentioning
confidence: 99%